Expression of Agrobacterium Homolog Genes Encoding T-complex Recruiting Protein under Virulence Induction Conditions - Yang, Jing; Wu, Meixia; Zhang, Xin; Guo, Minliang; Huang, Zhiwei (Frontiers in Microbiology, 2015)
The proteins encoded by three Agrobacterial genes, atu5117, atu4860, and atu4856, are highly homologous to each other in amino acid sequence. All three proteins can bind to VirD2 and are named VBP1, VBP2, and VBP3 (VirD2-binding protein), respectively. VBP is involved in T-DNA transfer by recruiting the T-complex from the cytosol to the polar transport apparatus T4SS (type IVsecretion system) and is defined as the “T-complex recruiting protein.” However, it remains unknown how these three homologous genes co-exist in a relatively small prokaryotic genome. To understand whether these three homologous genes are expressed differentially under virulence induction conditions, we examined the effects of virulence induction conditions, including various pH values, temperatures and acetosyringone (AS, an effective virulence inducer to Agrobacterium tumefaciens) concentrations, on the expression of the three VBP-encoding genes. Our data showed that vbp1 (atu5117) and vbp3 (atu4856) maintained constant expression under the tested induction conditions, whereas the expression of vbp2 (atu4860) was affected by the conditions. Culture conditions favorable to the expression of vbp2 differed from the reported induction conditions for other virulence proteins. In particular, the pH value was a crucial factor for the expression of vbp2. In addition, the deletion of vbp1 affected the expression of vbp2. Taken together, these results suggest that the mechanisms regulating the expression of these three homologous genes are different from the virulence induction mechanism and that VBP homologs are presumably involved in other biological processes in addition to T-complex recruitment.